Analisis Pengaruh Pengetahuan K3, Sikap K3, dan Kesadaran Berperilaku K3 Terhadap Produktivitas Kerja - Mahendra, Muhammad Oka; Putra, Al Fiillian Sah; Refiza, Hazazil Zabila (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The success of a project is greatly influenced by the productivity of its workers. K3 is an indicator of the success of a project. This study aims to determine the effect of K3 knowledge on work productivity, to determine the effect of K3 attitudes on work productivity, to determine the effect of K3 behavioral awareness on work productivity. This type of research uses quantitative methods. Data collection techniques using questionnaires, unstructured interviews, field observations and literature studies. The sample in this study were construction workers at two building construction project locations totaling 125 respondents. The data analysis method used is descriptive analysis, instrument testing (validity testing and reliability testing), classical assumption testing (normality testing), multiple linear regression coefficient testing, and hypothesis testing (t-test, f-test, and coefficient of determination). The magnitude of the influence that has been proven through the determination coefficient test for the independent variable is 18.7% on the dependent variable which can be concluded that the independent variable does not have a large influence.